Dris norms and critical leaf nutrient levels for ‘Niagara rosada’ grape in Jundiaí region, São Paulo (Brasil) - Junqueira Teixeira, Luiz Antonio; Tecchio, Marco Antonio [UNESP]; Moura, Mara Fernandes; Terra, Maurilo Monteiro; Paioli Pires, Erasmo Jose (Soc Brasileira Fruticultura, 2015)
Preliminary Diagnosis and Recommendation Integrated System (DRIS) norms and critical leaf nutrient levels (CLN) for 'Niagara Rosada'grape grafted on the rootstock 'IAC 766'growing in the region of Jundiai, State of Sao Paulo (Brazil) are presented. DRIS norms and CLN were established from a data bank of leaf nutrient concentration (N, P, K, Ca and Mg) and fruit yield with 116 records. The data bank gets information from fertilization experiments and from a field survey comprising four crop cycles. The data were divided into high-yielding (>26 t/ha) and low-yielding (<26 t/ha) subpopulations and norms were computed using standard DRIS procedures. Even with the diversity of cropping conditions, the relationship between the nutrient balance index from DRIS and fruit yield was highly significant (R-2 = 0.48, p<0.0001), indicating that part of the variation in productivity of vineyards can be credited to nutritional status of the plants. The CLNs were derived using multiple linear regressions relating to the foliar nutrient concentration with DRIS indices of all nutrients. The CLNs for N, P, K, Ca, and Mg were 38.0, 3.0, 11.4, 13.7, and 3.5 g/kg, respectively.

São apresentadas normas DRIS preliminares e derivados níveis críticos de nutrientes no tecido foliar (NC) para a videira ‘NiagaraRosada’ enxertada sobre o porta-enxerto ‘IAC 766’, nas condições de cultivo da região de Jundiaí-SP. As normas DRIS e os NCs foram obtidos a partir de um banco de dados com 116 registros, relacionando produtividade e teores foliares de N, P, K, Ca e Mg das videiras. Esses registros foram obtidos em experimentos de adubação e em um levantamento do estado nutricional de videiras realizados na região de Jundiaí, durante quatro ciclos de produção. Os registros foram separados em duas subpopulações: alto (>26 t/ha), e baixo rendimento (<26 t/ha) e as normas DRIS foram calculadas de acordo com os procedimentos convencionais. Mesmo com a diversidade nas condições de cultivo, a relação entre o índice de balanço nutricional e a produtividade das plantas foi altamente significativa (R2=0,48; p<0,0001), indicando que parte da variação na produtividade dos vinhedos pode ser creditada ao estado nutricional das plantas. Os NCs foram obtidos a partir de regressões múltiplas, relacionando teores foliares de cada nutriente com todos os índices DRIS. Os NCs para teores foliares de N, P, K, Ca e Mg foram 38,0; 3,0; 11,4; 13,7 e 3,5 g kg-1, respectivamente.
Normas dris e níveis críticos de nutrientes para videira ‘niagara rosada’ cultivada na região de Jundiaí-SP
Keywords: Plant analysis; Plant nutrition; Vitis spp.; Nutritional diagnose; Análise foliar; Uva; Fruticultura; Vitis spp.; Nutrição mineral; Ddiagnóstico nutricional